Resistances to productive thinking - Felipe, Abraham I. (Education Quarterly, 1958)
At certain points in our lives, a number of things become very important to accomplish. We have to avoid guilt or shame, achieve power, gain prestige, demonstrate our abilities or sense in ourselves our growing potentialities. At times, immediate satisfaction if urgent, and sex, excretion and other biological drives become paramount. And when these different points coincide temporarily with thinking productively which is not attractive or, at best, deters reaching these ends, shortcuts are sought, and we postpone or even abandon productive thinking for the activities that yield immediate results.